Heat and freezing pre-thermal treatments as a means of freeing potatoes from mosaic virus and its effects on potato plants quality characters - Younes, N. A.; El-Sheikh Aly, M. M.; Aboul-Nasr, M. H. (Journal of Phytopathology and Disease Management, 2014)
The aim of the study was to control of potato mosaic virus by using hot-air, hot-water and freezing as a physical pre-thermal treatments. Infected tubers of Lady Rosetta and Mondial potato (Solanum tuberosum L.) cultivars were treated by hot-air and hot-water treatments at 55± 2 ̊ C and freezing treatment at -18±2 ̊ C for 1, 2, 3 and 4 hours. Hot-air and freezing treatments showed complete elimination of mosaic virus from treated tubers. Hot-water treatment caused tuber damage at different exposure times. In this respect, hot-air treatment at 55± 2 ̊ C and freezing treatment at -18±2 ̊ C for two hours gave the best results of eliminating the virus from tubers and did not affect on economic characters of potato cultivars.